Sintesis Li1,37Mn2O4 Dengan Metoda Solid-State Reaction dan Hidrothermal (Synthesis of Li1,37Mn2O4 by Using Solid State Reaction and Hydrothermal Methods) - Etty Wigayati; Ibrahim Purawiardi (Metalurgi, 2018)
Li1.37Mn2O4 as cathode on Lithium ion battery has been synthesized by SSR (solid-state reaction) and HT (hydrothermal) methods. The starting materials used were Li2CO3 and MnO2 for SSR method, with a calcination temperature of 700 oC and a sintering temperature of 900 oC. For the HT method, the starting materials used were LiOH and MnO2, at temperature of 200 oC for 90 hours duration. XRD (x-ray diffraction) pattern of SSR sample shows that spinel cubic structure of Li1.33Mn1.667O4 and FCC (face-centered cubic) structure of LiMn2O4 occurs. For the HT sample, the phases that were formed are spinel cubic structure of Li1.37Mn2O4 and Mn3O4. We can see from the TEM (transmission electron spectroscopy) images, the sample which was synthesized by SSR method, the crystallite of spinel structure resembles to that of elongated multi-walled nanofiber, while the sample fabricated by HT method formed a multi-walled ring. The SEM (scanning electron microscopy) images show that most of the particles have both elongated and roundish ellipsoidal morphology and also distributed homogeneously. From the PSA (particle size analyzer) it can be seen that the sample synthesized by SSR method has particle size of 1278.3 nm, while the sample produced by HT method has particle size of 643.7 nm. Results of cathode battery test of Li1.37Mn2O4 with the use of battery cycler are shown in the cyclic voltammetrycurve which provides information on oxidation-reduction reactions. The charge-discharge measurement result shows that for Li1.37Mn2O4 (SSR), the charge and discharge capacity are 86.63 mAh/g and 85.98 mAh/g, respectively. These values are higher than those of Li1.37Mn2O4 sample fabricated by HT method which has charge capacity of 66.7 mAh/g and discharge capacity of 59.8 mAh/g. AbstrakTelah dilakukan sintesis senyawa Li1,37Mn2O4 melalui metoda solid state reaction(SSR) dan metoda hidrotermal(HT). Bahan awal yang dipergunakan adalah Li2CO3 dan MnO2 untuk metoda  solid state reaction, dengan temperatur kalsinasi 700oC dan temperatur sintering 900oC, Sedang untuk metoda hidrotermal bahan yang dipergunakan adalah LiOH dan MnO2, pada temperatur 200oC selama 90 jam. Li1,37Mn2O4  yang terbentuk akan dipergunakan sebagai katoda pada baterai Lithium ion. Dari pola difraksi XRD menunjukkan bahwa pada sintesis dengan metoda SSR fasa yang terbentuk menyerupai fasa Li1,33Mn1,667O4 dengan struktur kubik spinel dan dan FCC LiMn2O4. Hasil analisis sampel metoda HT menunjukan bahwa terbentuk fasa Li1,37Mn2O4 dengan struktur kubik spinel dan fasa Mn3O4. Dari gambar TEM metode sintesis SSR bentuk kristalit struktur spinel menyerupai multiwalled nanofiber memanjang, sedang sintesis HT membentuk multiwalled ring. Hasil analisis SEM menunjukkan bahwa morphologi partikel berbentuk pipih memanjang, dengan sebaran yang homogen. Dari analisis PSA dapat diketahui bahwa untuk sampel dengan metoda SSR mempunyai ukuran partikel 1278,3 nm, sedang sampel HT mempuyai ukuran partikel 643,7 nm. Uji baterai katoda Li1,37Mn2O4 dengan battery cycler ditunjukan dengan kurva siklik voltametrik, adanya proses oksidasi dan reduksi. Hasil pengukuran charge-discharge didapatkan kapasitas charge sekitar 86,63 mAh/gr, kapasitas discharge 85,98 mAh/gr pada Li1,37Mn2O4 (SSR) lebih tinggi dari kapasitas charge 66,7 mAh/gr kapasitas discharge 59,8 mAh/gr pada sampel Li1,37Mn2O4 (HT).